Pre-Equilibrium Clustering in Production of Spectator Fragments in Collisions of Relativistic Nuclei - Roman Nepeivoda; Aleksandr Svetlichnyi; Nikita Kozyrev; Igor Pshenichnov (Particles, 2022)
An algorithm of pre-equilibrium clustering of spectator matter based on the construction of the minimum spanning tree (MST) is presented. The algorithm was implemented in the Abrasion-Ablation Monte Carlo for Colliders (AAMCC) model designed to study the characteristics of spectator matter in collisions of relativistic nuclei. Due to accounting for the pre-equilibrium clusters in modelling <semantics>208</semantics>Pb–<semantics>208</semantics>Pb collisions at the LHC, the agreement of simulation results with experimental data on the average multiplicities of spectator nucleons was improved. The results of the AAMCC-MST were compared with experimental data on the interactions of <semantics>197</semantics>Au nuclei in nuclear photoemulsion. Comparison of the yields of spectator nuclei calculated for <semantics>16</semantics>O–<semantics>16</semantics>O collisions with the yields measured in interactions of <semantics>16</semantics>O with light nuclei of photoemulsion made it possible to estimate the effect of MST-clustering in small nuclear systems.